2020
DOI: 10.1021/acs.est.9b07781
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RNA Interference (RNAi) Biopesticides: Double-Stranded RNA (dsRNA) Extraction from Agricultural Soils and Quantification by RT-qPCR

Abstract: Double-stranded RNA (dsRNA) molecules are used as a novel class of biopesticides. To enable assessments of the ecological risk associated with their release to receiving environments, we developed an approach to quantify dsRNA in agricultural soils using quantitative reverse transcription-polymerase chain reaction (RT-qPCR). To allow quantification of dsRNA adsorbed to particles, we also developed a protocol to transfer dsRNA from particles to the extraction buffer by changing particle surface charge and addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…The resultant liquid was stored at −20 °C until use. For experiments using RNase from soil, we mixed a slurry prepared with 50 g of fine sandy loam soil (characterized previously 40 ) and 50 mL of sterile water in an uncovered 250 mL Erlenmeyer flask using a stir bar (1000 rpm) at 24 °C for 2 days. We then centrifuged the slurry at 21,100g for 1 min and collected the supernatant.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The resultant liquid was stored at −20 °C until use. For experiments using RNase from soil, we mixed a slurry prepared with 50 g of fine sandy loam soil (characterized previously 40 ) and 50 mL of sterile water in an uncovered 250 mL Erlenmeyer flask using a stir bar (1000 rpm) at 24 °C for 2 days. We then centrifuged the slurry at 21,100g for 1 min and collected the supernatant.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Kimberly Parker, assistant professor of environment and chemical engineering at Washington University, has had to come up with an entirely new technique to detect particles of dsRNA in the environment because they are much larger than the molecules in traditional pesticides (7). "Our big concerns are actually understanding what happens to them in the environment and how they undergo different degradation processes," she says.…”
Section: After Effectsmentioning
confidence: 99%
“…SIGS using naked dsRNA has been shown to be an effective control method against both insect pests and fungal pathogens [31,52,108]. Despite these advances, topically applied dsRNA molecules are vulnerable to degradation.…”
Section: Dsrna Formulationsmentioning
confidence: 99%
“…A number of studies in both fungi and insects have demonstrated the effectiveness of this technology [31,45,49,50]. Unlike many chemical pesticides, environmental persistence of dsRNAs appears to be limited, which, from an environmental protection perspective, is an attractive feature [51,52]. Studies have shown a half-life of less than 24 h for dsRNA within the soil, due primarily to bacterial degradation [51].…”
Section: Introductionmentioning
confidence: 99%